A characterization of minimum price Walrasian rule in object allocation problem for an arbitrary number of objects - Ryosuke Sakai; Shigehiro Serizawa (Osaka University, Institute of Social and Economic Research (ISER), 2021)
We consider the multi-object allocation problem with monetary transfers where each agent obtains at most one object (unit-demand). We focus on allocation rules satisfying individual rationality, no subsidy, efficiency, and strategy-proofness. Extending the result of Morimoto and Serizawa (2015), we show that for an arbitrary number of agents and objects, the minimum price Walrasian is characterized by the four properties on the classical domain.
Keywords: D82; D47; D63; 330; Multi-object allocation problem; Strategy-proofness; Efficiency; Minimumprice Walrasian rule; Non-quasi-linear preference; Heterogeneous objects